CHURCH MUSIC: THE CONNECTION BETWEEN FRIEDRICH NIETZSCHEŽS QUOTATION 'WITH NO MUSIC, LIFE WOULD BE AN ERROR' - Toni; Jordi Istandar, Bayu Erlangga Cendana, Andre Sebastian, Jesica Agnesia Keren, Jonathan Salmanezer, O (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2023)
The aim of this research is to provide a descriptive analysis of music that transcends the boundaries of Friedrich Nietzsche's philosophy, particularly in relation to church music. The study focuses on church music as both a form of worship and a discipline. Qualitative research methods were employed, with data gathered from literature, secondary sources, and published journals that discuss music, Friedrich Nietzsche, and church music. The results indicate that music has a significant role in church music and as a scientific discipline. It is viewed as part of Friedrich Nietzsche's philosophy, which aims to demonstrate the centrality of music in the axiological thermality of worship spaces and daily life practices.